Reference Ranges for Regional Cerebral Oxygen Saturation with Masimo O3 after Birth and Differences with Other Devices - Carnicero, Luis Bachiller; Carbonero, Sonia Caserío (American Journal of Perinatology, 2024)
Objective Cerebral oximetry using near-infrared spectroscopy (NIRS) is a noninvasive optical technology widely used in neonatology. The present study aimed to define reference ranges for cerebral tissue oxygen saturation (crSO2) with a new four-wavelength NIRS device, Masimo O3 oximeter, during immediate transition after birth and compare values with those obtained previously with NIRO 200NX®.Study Design This was a prospective observational study using Masimo O3 device to measure crSO2 and regional cerebral fractional tissue oxygen extraction (cFTOE) in healthy term newborns delivered by primary cesarean section, during the 15 minutes after cord clamping. The neonates who required any medical support were excluded. The NIRS sensor was placed on the right forehead. Peripheral oxygen saturation and heart rate were continuously measured by pulse oximetry. Previous studies which established centiles for crSO2 with NIRO 200NX were used for comparison.Results A total of 44 newborns were included. The median crSO2 and cFTOE (interquartile range) at 2, 5, and 7 minutes was 54% (49–54), 71% (64–86), and 79% (73–84) and 0,25 (0,18–0,33), 0,19 (0,15–0,23), and 0,16 (0,12–0,21), respectively, with no further changes afterwards. The crSO2 measurements were significantly higher with Masimo O3 compared with NIRO-200NX.Conclusion The present observational study presented reference ranges for crSO2 and cFTOE measured with Masimo O3 oximeter during the immediate neonatal transition. Values obtained with O3 were higher than those obtained with other oximeters. For this reason, crSO2 is device-specific so there must be known reference values for each oximeter to define therapeutic interventions based on crSO2 and assess cerebral oxygenation in clinical studies.Key Points
Keywords: near-infrared spectroscopy; newborn infant; cerebral tissue oxygen saturation; birth; term newborn